Investigating the potential of magnetic are oscillated GMWA - welding for hard surfacing applications - Nagel, Falk (2012)
The flux cored arc welding process has some characteristic features and is therefore established in the industry to fabricate hardfacing. One advantage of the process is the possibility to vary the alloy content of the weld metal by manipulating the chemical composition of the filler material. Moreover, it is possible to produce self shielding electrodes, which show advantages for outdoor applications. One the other hand this process creates high dilution rates. One possibility to avoid this effect is to apply a magnetic field in order to deflect the welding arc. In this thesis, the influence of a transversal magnetic field on the weld seam formation during FCAW was investigated. An increase of the weld width and a simultaneous decrease of the penetration depth was achieved at a certain deflection. The influence of the magnetic oscillation was found to be stronger for short circuit mode than for pulsed mode. Furthermore, high frequencies in combination with a high magnetic flux density caused a reduced process stability and consequently a worsening of the weld bead appearance. Apart from that, the drop detachment was inhibited, when a strong magnetic field was applied during pulsed and spray mode.